2013
DOI: 10.1016/j.radonc.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing-sparing intensity-modulated radiotherapy for head and neck cancer patients: Treatment planning optimization and clinical introduction

Abstract: The benefit of SW-IMRT depends significantly on neck radiotherapy, tumour site and the amount of overlap between SWOARs and PTVs. Optimal clinical introduction requires a detailed evaluation and comparison between the standard (ST-IMRT) and new technique (SW-IMRT) in order to fully exploit the potential benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…It has been reported that the rate of xerostomia also critically depends on the irradiation of sub-maxillary gland and minor salivary glands distributed throughout the head and neck mucosa [30][31][32]. Similarly, it has been shown that the rate of radiation-induced dysphagia also critically depends on the amount of constrictor muscle included in the high dose region [33][34][35]. Altogether, it is reasonable to hypothesize that the use of FDG-PET could also somehow reduce the radiation dose at the level of these critical organs at risk, at least in case of oropharyngeal tumors, and thus further reduce the rate of late morbidity after radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the rate of xerostomia also critically depends on the irradiation of sub-maxillary gland and minor salivary glands distributed throughout the head and neck mucosa [30][31][32]. Similarly, it has been shown that the rate of radiation-induced dysphagia also critically depends on the amount of constrictor muscle included in the high dose region [33][34][35]. Altogether, it is reasonable to hypothesize that the use of FDG-PET could also somehow reduce the radiation dose at the level of these critical organs at risk, at least in case of oropharyngeal tumors, and thus further reduce the rate of late morbidity after radiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…A number of authors reported on radiation delivery technologies aiming at optimizing the dose to swallowing organs at risk [12][13][14][15][16][17]. Amin et al showed that by using IMRT planning to reduce the dose to the pharyngeal constrictor muscles and the larynx and esophageal inlet muscle, the duration of PEG-tube dependence could be reduced by 4.9 months [18].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for preventing swallowing dysfunction is to reduce the dose to anatomical structures that are important for swallowing by using advanced radiation delivery techniques such as intensity modulated radiotherapy (IMRT) [12][13][14][15][16][17][18]. However, radiotherapy treatment optimization requires information on the most important dose-volume parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This multivariable NTCP model enables identification of patients at risk for late dysphagia and the development of new radiation delivery techniques, such as swallowing sparing intensity modulated RT (SW-IMRT) [7,8].…”
mentioning
confidence: 99%